KAJIAN DASAR PERENCANAAN DAN PELAKSANAAN JEMBATAN PELENGKUNG BETON - Lanneke Tristanto; Redrik Irawan (Jurnal Jalan-Jembatan, 2010)
The arch of an arch bridge structure is mainly a compression member with curved linier parabolic shape. A great part of the uniform and moving loads is carried by compression forces prevent and reduce concrete tensioning due to traffic passage on the bridge. Existing old arch bridges still resist the increasing vehicle loads due to reserve capacity of the comperession member. Arch bridges reduce 15% concrete volume compared to straight girder bridges, so they are economical in dimensionand reinforcement. Arch bridges are classified into two types according to the thrust force transmission. The rigid arch type is optimal for very good soil conditions as the thrust force is directly transmitted to very good foundation soil. The stiffened arch type is suitable for deep foundation condition as the thrust force is carried by the structural tie beam. The monolithic system between super and sub structures with the number of plastic hinges improve the earthquake resistance. The construction of arch bridge always involves the need for formwork that is removed after the arch is connected and the compression line has been formed. An improperly connected arch will fail at the time of formwork removal. The maximum reinforced concrete arch span 90 m is efficient compared to the maximum prestressed concrete girder span 45 m. Composite reinforced concrete arch bridges with steel truss/profile for scaffolding as well reinforcement reach (90-245)m span. Key words : arch bridge, rigid arch, stiffened arch, thrust, compression line